2015
DOI: 10.1590/1516-4446-2014-1496
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant effects of a single dose of ayahuasca in patients with recurrent depression: a preliminary report

Abstract: Objectives: Ayahuasca (AYA), a natural psychedelic brew prepared from Amazonian plants and rich in dimethyltryptamine (DMT) and harmine, causes effects of subjective well-being and may therefore have antidepressant actions. This study sought to evaluate the effects of a single dose of AYA in six volunteers with a current depressive episode. Methods: Open-label trial conducted in an inpatient psychiatric unit. Results: Statistically significant reductions of up to 82% in depressive scores were observed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
311
0
27

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(374 citation statements)
references
References 35 publications
11
311
0
27
Order By: Relevance
“…Three pilot studies using psychedelics in major depressive disorder have been published to date in the modern literature (Carhart-Harris et al, 2017, 2016aOsorio et al, 2015;Sanches et al, 2016). Our own open-label pilot study gave 2 doses of psilocybin (a 10 mg "test" dose and a 25 mg therapeutic dose) 1 week apart with psychological support before and after the experience to 20 patients with treatment resistant depression who were moderately to severely depressed, but without psychotic features (Carhart-Harris et al, 2017, 2016a.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three pilot studies using psychedelics in major depressive disorder have been published to date in the modern literature (Carhart-Harris et al, 2017, 2016aOsorio et al, 2015;Sanches et al, 2016). Our own open-label pilot study gave 2 doses of psilocybin (a 10 mg "test" dose and a 25 mg therapeutic dose) 1 week apart with psychological support before and after the experience to 20 patients with treatment resistant depression who were moderately to severely depressed, but without psychotic features (Carhart-Harris et al, 2017, 2016a.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
“…Flavia de Lima Osorio and colleagues (Osorio et al, 2015) and Rafael Sanches and colleagues (Sanches et al, 2016), both working in Sao Paulo, Brazil, reported studies where a single dose of ayahuasca to patients with recurrent depression. In Osorio's pilot study, 6 medication and ayahuasca naive participants (4 women) were given 2.2 ml/kg of a standardised preparation of ayahuasca containing 0.8 mg/ml DMT and 0.21 mg/ml of harmine.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
“…Ayahuasca is an Amazonian botanical hallucinogenic cook. It contains dimethyltryptamine, a 5-HT2A receptor agonist, and harmine, a monoamine-oxidase A inhibitor [10,11] As a partial agonist of mu opioid receptor, buprenorphine can diminish the level of depression and suicidal thoughts rapidly [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…46 É necessário frisar que a etiologia da depressão é desconhecida e que os tratamentos farmacológicos existentes baseiam-se no conhecimento que se tem dos fatores neurofisiológicosimplicados (OSÓRIO et al 2015). Talvez o limite da precisão etiológica resida justamente na dificuldade em compreender como os aspectos neurofisiológicos e psicossociais se correlacionam na constituição do quadro depressivo.…”
unclassified
“…63 Nas pesquisas experimentaismencionadas,o controle laboratorial serve para diferenciar, por exemplo, se os efeitos terapêuticos são uma consequência das propriedades químicas da ayahuasca ou da vivência comunitária no contexto religioso (SANTOS et al, 2016, p. 70 67 A aposta científica nas propriedades anti-depressivas da ayahuasca é explicitamente justificadapela necessidade de novas drogas antidepressivas que tenham menos efeitos colaterais e sejam mais eficazes na redução da sintomatologia da ansiedade e da depressão (SANTOS et al 2016;OSÓRIO et al 2015). Embora o motivo seja nobre, dado os indíces crescentes da depressão e dos prejuízos humanos causados, ainda não está claro para mim: em que consistiria o uso farmacológico da ayahuasca?…”
unclassified